(3cJGH aVd GdUdGI Ydi GdfHi Udi Gddg Ydjg hSdes - (3ESeGYjd Hf ESMGb Hf ESeGYjd Hf MeGO Hf RjO GdLgVej GdGROj,J (B282 (3g` s
(3ChdgG (B:s
(3MOKfi CNj Yf SdjeGf Hf HdGd Yf YHjO Gddg Hf YeQ Yf KGHJ bGd CfSi Hf eGdc bGd CHh WdMI Cf QShd Gddg Udi Gddg Ydjg hSde NQL Ydjge jYahf GdHTQ ai hLgg s
(3BNQgG (B:s
(3MOKfi CHj Yf bJGOI Yf YHjO Gddg Hf GdMGQK eYGP cGf jUdi Ydi GdfHi Udi Gddg Ydjg hSde hbJ GdbfhJ s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B310s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs